Implementasi Kebijkan Pencegahan Pernikahan Di Bawah Umur Di Desa Soni Kecamatan Dampal Selatan Kabupaten Toli-Toli - Husain, Husni; Natsir, Nawawi; Mayusa, Askar (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
Data on underage marriages in Soni Village has increased over the past 3 years. In 2020, the number of underage marriages reached 3.4% and in 2021 it reached 4%, and in 2022 it increased significantly, reaching 20.6%, with an average age of 18 years and under. This study aims to determine the implementation of the policy to prevent underage marriages in Soni Village, Tolitoli Regency. According to Van Meter and Van Horn, the implementation of the policy consists of 6 aspects, namely policy standards and objectives, resources, communication between implementing organizations, characteristics of implementing agents, attitudes of implementers, social, economic and political environments. The research method used is descriptive qualitative, with 5 informants. The results of this study indicate that the implementation of the policy to prevent underage marriages in Soni Village, Tolitoli Regency has not been running optimally. Aspects of standards and policy objectives, there needs to be an affirmation at the level of implementing related policies that must be used as a reference, and from the resources it is not yet sufficient to be seen from the budgeting aspect that is not available, and communication between organizations and effectiveness is not yet optimal due to the absence of formal socialization and through media demonstration tools, and from the social, economic and political environment it has not run well because From the social environment it has not run well because there are still many social problems such as pregnancy outside of marriage, arranged marriages, and stories of community understanding in underage marriage to marrying off their children according to them it is the best solution to continuing education. And the lack of political encouragement for the budget planning process in the policy.